Analysis of gender barriers in the design and implementation of climate change related policy for agriculture and food security in Burkina Faso - Laeticia, D. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
The fourth assessment report of the Intergovernmental Panel on Climate Change (IPCC) in 2007, stated that climate change impacts will differ according to gender. It also highlights that most studies of climate change impacts tend to group countries or populations together and ignore differences within groups such as gender. Burkina Faso is not an exception. Studies have shown that, given equal access to resources and expertise, women often achieve higher yields than men. In fact, women farmers are responsible for as much as 70% of the agricultural output that feeds African families (World Bank, 1989) and contribute approximately 46% of Africa’s farm labor. In addition, women contribute 90% of food processing, fetching water and fuel; 80% of food storage and transport; 90% of the work of hoeing and weeding and 60% of harvesting (Blackden and Bhanu, 1999). These results were obtained by women as they had not fairly access to resources than men. Gender-aware approaches to climate adaptation that seek to improve women’s adaptive capacity will benefit not just to women, but the household they are part of and the people they are responsible for. There is a need to understand how to improve women’s adaptive capacity and learn how to support women against climate threats. This will imperatively help to address the equitable access to climate-proof technologies for men and women in Burkina Faso.